Welcome to Westonci.ca, the place where your questions are answered by a community of knowledgeable contributors. Our platform provides a seamless experience for finding reliable answers from a network of experienced professionals. Experience the ease of finding precise answers to your questions from a knowledgeable community of experts.
Sagot :
To determine which equations accurately represent the data in the given table, we need to substitute each data pair [tex]\((x, y)\)[/tex] into each equation and check if the equation holds true.
Let's go through each equation step-by-step:
1. First Equation: [tex]\( y - 6 = \frac{-5}{4}(x + 2) \)[/tex]
We will substitute each [tex]\((x, y)\)[/tex] pair:
- For [tex]\((x = -2, y = 6)\)[/tex]:
[tex]\[ 6 - 6 = \frac{-5}{4}(-2 + 2) \Rightarrow 0 = 0 \quad \text{(This is true)} \][/tex]
Since this pair satisfies the equation, it represents the data.
2. Second Equation: [tex]\( y - 2 = \frac{-5}{4}(x - 1) \)[/tex]
Let's substitute each [tex]\((x, y)\)[/tex] pair:
- For [tex]\((x = 0, y = 3.5)\)[/tex]:
[tex]\[ 3.5 - 2 = \frac{-5}{4}(0 - 1) \Rightarrow 1.5 = 1.25 \quad \text{(This is false)} \][/tex]
- For [tex]\((x = 2, y = 1)\)[/tex]:
[tex]\[ 1 - 2 = \frac{-5}{4}(2 - 1) \Rightarrow -1 = -1.25 \quad \text{(This is false)} \][/tex]
None of the pairs satisfy the equation, so it does not represent the data.
3. Third Equation: [tex]\( y + 2 = \frac{-5}{4}(x - 6) \)[/tex]
Substituting each [tex]\((x, y)\)[/tex] pair:
- For [tex]\((x = 0, y = 3.5)\)[/tex]:
[tex]\[ 3.5 + 2 = \frac{-5}{4}(0 - 6) \Rightarrow 5.5 = 7.5 \quad \text{(This is false)} \][/tex]
- For [tex]\((x = 2, y = 1)\)[/tex]:
[tex]\[ 1 + 2 = \frac{-5}{4}(2 - 6) \Rightarrow 3 = 5 \quad \text{(This is false)} \][/tex]
None of the pairs satisfy the equation, so it does not represent the data.
4. Fourth Equation: [tex]\( y - 1 = \frac{-5}{4}(x - 2) \)[/tex]
Substituting each [tex]\((x, y)\)[/tex] pair:
- For [tex]\((x = 2, y = 1)\)[/tex]:
[tex]\[ 1 - 1 = \frac{-5}{4}(2 - 2) \Rightarrow 0 = 0 \quad \text{(This is true)} \][/tex]
Since this pair satisfies the equation, it represents the data.
5. Fifth Equation: [tex]\( y - 3.5 = -1.25 x \)[/tex]
Substituting each [tex]\((x, y)\)[/tex] pair:
- For [tex]\((x = 0, y = 3.5)\)[/tex]:
[tex]\[ 3.5 - 3.5 = -1.25(0) \Rightarrow 0 = 0 \quad \text{(This is true)} \][/tex]
Since this pair satisfies the equation, it represents the data.
In summary, the equations that represent the data in the table are:
[tex]\[ y - 6 = \frac{-5}{4}(x + 2) \][/tex]
[tex]\[ y - 1 = \frac{-5}{4}(x - 2) \][/tex]
[tex]\[ y - 3.5 = -1.25 x \][/tex]
Thus, the equations that apply are the first, fourth, and fifth equations.
Let's go through each equation step-by-step:
1. First Equation: [tex]\( y - 6 = \frac{-5}{4}(x + 2) \)[/tex]
We will substitute each [tex]\((x, y)\)[/tex] pair:
- For [tex]\((x = -2, y = 6)\)[/tex]:
[tex]\[ 6 - 6 = \frac{-5}{4}(-2 + 2) \Rightarrow 0 = 0 \quad \text{(This is true)} \][/tex]
Since this pair satisfies the equation, it represents the data.
2. Second Equation: [tex]\( y - 2 = \frac{-5}{4}(x - 1) \)[/tex]
Let's substitute each [tex]\((x, y)\)[/tex] pair:
- For [tex]\((x = 0, y = 3.5)\)[/tex]:
[tex]\[ 3.5 - 2 = \frac{-5}{4}(0 - 1) \Rightarrow 1.5 = 1.25 \quad \text{(This is false)} \][/tex]
- For [tex]\((x = 2, y = 1)\)[/tex]:
[tex]\[ 1 - 2 = \frac{-5}{4}(2 - 1) \Rightarrow -1 = -1.25 \quad \text{(This is false)} \][/tex]
None of the pairs satisfy the equation, so it does not represent the data.
3. Third Equation: [tex]\( y + 2 = \frac{-5}{4}(x - 6) \)[/tex]
Substituting each [tex]\((x, y)\)[/tex] pair:
- For [tex]\((x = 0, y = 3.5)\)[/tex]:
[tex]\[ 3.5 + 2 = \frac{-5}{4}(0 - 6) \Rightarrow 5.5 = 7.5 \quad \text{(This is false)} \][/tex]
- For [tex]\((x = 2, y = 1)\)[/tex]:
[tex]\[ 1 + 2 = \frac{-5}{4}(2 - 6) \Rightarrow 3 = 5 \quad \text{(This is false)} \][/tex]
None of the pairs satisfy the equation, so it does not represent the data.
4. Fourth Equation: [tex]\( y - 1 = \frac{-5}{4}(x - 2) \)[/tex]
Substituting each [tex]\((x, y)\)[/tex] pair:
- For [tex]\((x = 2, y = 1)\)[/tex]:
[tex]\[ 1 - 1 = \frac{-5}{4}(2 - 2) \Rightarrow 0 = 0 \quad \text{(This is true)} \][/tex]
Since this pair satisfies the equation, it represents the data.
5. Fifth Equation: [tex]\( y - 3.5 = -1.25 x \)[/tex]
Substituting each [tex]\((x, y)\)[/tex] pair:
- For [tex]\((x = 0, y = 3.5)\)[/tex]:
[tex]\[ 3.5 - 3.5 = -1.25(0) \Rightarrow 0 = 0 \quad \text{(This is true)} \][/tex]
Since this pair satisfies the equation, it represents the data.
In summary, the equations that represent the data in the table are:
[tex]\[ y - 6 = \frac{-5}{4}(x + 2) \][/tex]
[tex]\[ y - 1 = \frac{-5}{4}(x - 2) \][/tex]
[tex]\[ y - 3.5 = -1.25 x \][/tex]
Thus, the equations that apply are the first, fourth, and fifth equations.
Thanks for stopping by. We strive to provide the best answers for all your questions. See you again soon. Thank you for choosing our platform. We're dedicated to providing the best answers for all your questions. Visit us again. We're glad you visited Westonci.ca. Return anytime for updated answers from our knowledgeable team.